Epinephelus quinquefasciatus ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Epinephelus quinquefasciatus (Bocourt, 1868). Pacific Goliath Grouper or Jewfish. To 250 cm (98.4 in) TL (Robertson and Allen 2002). Bahía Almejas (24°22’N, 111°42’W), southern Baja California (Personal communication: Scripps Institution of Oceanography Fish Collection, La Jolla, California) and Gulf of California (Heemstra in Fischer et al. 1995) to Máncora, Peru (Chirichigno and Vélez 1998). Depth: intertidal to 100 m (328 ft) (min.: Personal Communication: Scripps Institution of Oceanography Fish Collection, La Jolla, California; max.: Craig et al. 2011). Also found in fresh water (Greenfield and Thomerson 1997). Previously considered Epinephelus itajara (Lichtenstein 1822), now known to be a species limited to the Atlantic Ocean (Craig et al. 2009). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 146, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...